ANALYSIS OF THE DRIVER’S POSITION IN THE TRAFFIC SYSTEM AND THE INFLUENCE ON THE LEVEL OF TRAFFIC SAFETY - Tursunov D. M. (Web of Journals Publishing, 2024)
Improvement of the mechanism of driver training and assessment of its impact on ensuring traffic safety and implementation of modern methods of driver training.
Keywords: Road, pedestrian, safety, transport, incident, speed.